Effect of the Entrance year in the Performance of Village Extension Worker in North Kordofan Rural Development Project (NKRDP) - E.Maruod, Maruod; Gaafar B. Suliman; Mekki A. A. El Maleih; Mohammed Y.Abdalla; Elzubair E. Elzain (IJRDO - Journal of Social Science and Humanities Research, 2019)
The current study was conducted in Um Ruwaba and Bara localities in North Kordofan State during 2006. The main objective of the study was to investigate the effect of entrance year in the role of the Village Extension Worker (VEW) on increasing the awareness of the community towards IPM techniques. The primary data were collected via questionnaires. Stratified random sampling technique was used to select 142 participants and 30 VEWs as a sample size. The data were analyzed using descriptive statistical analysis methods such as, frequency table; cross-tabulation and Chi-square. The results showed that the number of fields visits conducted during entrance year was only 35 and increased in unstable manner from 71% to 91.4% in year 2003 and 2004, respectively (p<0.05).The results recorded that in year 2004 the VEW was able to conduct more than twice village meetings per month (65.7%) compared with only 13% in entrance year(p<0.05).During 2004 the regular conducted campaigns represented 88.6% where as in entrance year and second years were only 52.2% & 57% respectively. The high level of significance (p< 0.05).The results explained that 12.5%, 16.7%, 33.3% and 37.5% were the percentage number of farmers trained by the VEW during the years entrance year, 2002, 2003 and 2004, respectively (p>0.05). As stated by the respondents, this could be attributed to the scarcity of the training materials, high illiteracy rate, and lack of desire among some farmers. The study recommends that more attention should be given to vegetables IPM in North Kordofan State where chemicals are used in inappropriate manner.